STUDI KASUS IMBANGAN ANGKUTAN SEDIMEN DI KALI PUTIH - Darmono, Rizal Gunawan (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT This study aims to find out the volume of a flood plan and balance between sediment raised in the mining of sand and sediment that comes in the time of flooding in kali Putih river’s area regional of Srumbung. The method of study is using observation method, interview method, and literature method. Hydrology data used in this study is map kali Putih river, map rain stasiun, and gradation of sand grains. To calculate the volume of a flood plan is using the rational method, weduwen method, and hasper method. And to calculate sediment transport using Mayer, Peter and Muller formulation. The calculation based on 5 rain station Argomulyo, G.maron, Ngepos, Babadan, and Kaliadem station using (1) Rasional, (2) Weduwen and (3) Hasper to 5 year reissue period are: (1) 233,94 m3/sec, (2) 80,67 m3/sec, (3) 129,48 m3/sec. Tthe result of the calculation of sediment transport using Meyer, Petter and Muller formulation produces sediment transport base for the entire widht of the river of 4,66 m3/second, and base sediment transport for 1 hour of 16776 m3.From the result of mining sediment of Srumbung area is 492750 m3/year. So the mining was done in Srumbung for 1 year is 492750 m3can be offset by during floods for 11,54 hours resulting heaps of 493214,4 m3.